KEMAMPUAN FLUENCY, FLEXIBILITY, ORGINALITY, DAN SELF CONFIDENCE SISWA SMP - Fahmi Nur Islami; Gita Dwi Putri; Putri Nurdwiandari (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
Creative thinking is a process of thinking that produces a wide variety of possible ideas and ways. The creative thinking indicator used consists of fluency, flexibility, originality, dan elabolasi. In addition to creative thinking beliefs about oneself determine how people think, feel, and motivate themselves in acting. This study aims to analyze the ability of creative thinking and self confidence of students on the material of cubes and beams. The research method used is qualitative descriptive. Subjects in this study were students of class IX in junior Darul Falah as many as 29 people. Based on the data analysis, it is concluded that the students' mathematical creative thinking ability is still low and there are still students who are less confident in learning mathematics.